Measured dynamic properties for FRP footbridges and their critical comparison against structures made of conventional construction materials. (1st September 2019) - Wei, Xiaojun; Russell, Justin; Živanović, Stana; Toby Mottram, J.
Abstract: This paper reports new experimental data for dynamic properties (i.e. modal mass, natural frequency and damping ratio) of eight FRP composite footbridges in Europe, which helps to resolve the weakness in knowledge and understanding of dynamic properties of FRP footbridges. In addition, dynamic properties are reviewed with the results of six other FRP footbridges and 124 non-FRP footbridges built after 1991. A comprehensive comparison of these 138 sets of dynamic properties shows that FRP footbridges possess similar fundamental frequencies at the same span, but usually higher damping ratios (mean of 2.5% c.f. mean of <1.0% for steel, concrete and steel-concrete composite). Additionally, natural frequencies and damping ratios identified from free decays measured on FRP footbridges are response amplitude dependent. Comparing the accelerance peaks of FRP and conventional footbridges revealed that the FRP footbridges are, on average, around 3.5 times more responsive to resonant excitation than the conventional bridges having the same bridge length, deck width and mode shape due to their significantly lower modal mass.